Renal angiomyolipoma - Çalışkan,Selahattin (2019)
SUMMARY INTRODUCTION Angiomyolipoma is one of the most common benign solid renal tumors. We investigated the characteristics of renal angiomyolipomas and the clinical outcomes of patients in the last thirteen years. METHODS The medical records of the patients who underwent nephrectomy were reviewed retrospectively from July 2005 to May 2018. The laboratory data, radiology, and pathology reports were recorded. Patients diagnosed with angiomyolipoma were included in the study. RESULTS A total of 28 patients were included in the study, eight of them male. The mean age of the patients was 55.89+14.49 years. The patients were treated with open and laparoscopic techniques. Partial nephrectomy was performed in 12 patients(42.85%). After pathological examination, 23 patients were diagnosed as fat rich, four patients as fat poor, and one as epithelioid angiomyolipoma. There were no recurrences in the follow-up 91.21+48.31 months. CONCLUSION Angiomyolipoma is a rare renal tumor in daily urology practice. Clinicians must be aware of its complications and manage patients well.